Mechanisms of Cell Entry by dsRNA Viruses: Insights for Efficient Delivery of dsRNA and Tools for Improved RNAi-Based Pest Control - Swevers, Luc; Kontogiannatos, Dimitrios; Kolliopoulou, Anna; Ren, Feifei; Feng, Min; Sun, Jingchen (Frontiers in Physiology, 2021)
While RNAi is often heralded as a promising new strategy for insect pest control, a major obstacle that still remains is the efficient delivery of dsRNA molecules within the cells of the targeted insects. However, it seems overlooked that dsRNA viruses already have developed efficient strategies for transport of dsRNA molecules across tissue barriers and cellular membranes. Besides protecting their dsRNA genomes in a protective shell, dsRNA viruses also display outer capsid layers that incorporate sophisticated mechanisms to disrupt the plasmamembrane layer and to translocate core particles (with linear dsRNA genome fragments) within the cytoplasm. Because of the perceived efficiency of the translocation mechanism, it is well worth analyzing in detail the molecular processes that are used to achieve this feat. In this review, the mechanism of cell entry by dsRNA viruses belonging to the Reoviridae family is discussed in detail. Because of the large amount of progress in mammalian versus insect models, the mechanism of infections of reoviruses in mammals (orthoreoviruses, rotaviruses, orbiviruses) will be treated as a point of reference against which infections of reoviruses in insects (orbiviruses in midges, plant viruses in hemipterans, insect-specific cypoviruses in lepidopterans) will be compared. The goal of this discussion is to uncover the basic principles by which dsRNA viruses cross tissue barriers and translocate their cargo to the cellular cytoplasm; such knowledge subsequently can be incorporated into the design of dsRNA virus-based viral-like particles for optimal delivery of RNAi triggers in targeted insect pests.